The Index of Prohibited Books four centuries of struggle over word and image for the greater glory of God - Vose, Robin J. E. (London Reaktion Books, 2022)
The first comprehensive history of the Catholic Church’s notorious Index, with resonance for ongoing debates over banned books, censorship, and free speech. For more than four hundred years, the Catholic Church’s Index Librorum Prohibitorum struck terror into the hearts of authors, publishers, and booksellers around the world, while arousing ridicule and contempt from many others, especially those in Protestant and non-Christian circles. Biased, inconsistent, and frequently absurd in its attempt to ban objectionable texts of every conceivable description—with sometimes fatal consequences—the Index also reflected the deep learning and careful consideration of many hundreds of intellectual contributors over the long span of its storied evolution. This book constitutes the first full study of the Index of Prohibited Books to be published in English. It examines the reasons behind the Church’s attempts to censor religious, scientific, and artistic works, and considers not only why this most sustained of campaigns failed, but what lessons can be learned for today’s debates over freedom of expression and cancel culture.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Index Librorum Prohibitorum; Index Librorum Prohibitorum; Prohibited books -- History; Censorship -- Religious aspects -- Catholic Church; Censorship ; Religious aspects ; Catholic Church; Prohibited books; History